2012
DOI: 10.1128/aem.01245-12
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Approach To Modeling Bacterial Lag Time, Using Logistic Regression as a Function of Time, Temperature, pH, and Sodium Chloride Concentration

Abstract: ABSTRACTThe objective of this study was to develop a probabilistic model to predict the end of lag time (λ) during the growth ofBacillus cereusvegetative cells as a function of temperature, pH, and salt concentration using logistic regression. The developed λ model was subsequently combined with a logistic differential equation to simulate bacterial numbers over time. To develop a novel model for λ, we determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…It has been shown that the maximum specific growth rate (μ max ) is reciprocally proportional to the lag time (λ) (Baranyi and Roberts, 1994;Koutsoumanis et al, 2006;McMeekin et al, 1993;Zwietering et al, 1994a). Although the product μ max × λ is not always constant (Koseki and Nonaka, 2012), it generally ranges between approximately 0 and 4 (Koutsoumanis et al, 2006;Zwietering et al, 1994a). In the present study, the lag time was estimated assuming that μ max × λ = 1 and μ max × λ = 4.…”
Section: Validation Of Modelmentioning
confidence: 96%
“…It has been shown that the maximum specific growth rate (μ max ) is reciprocally proportional to the lag time (λ) (Baranyi and Roberts, 1994;Koutsoumanis et al, 2006;McMeekin et al, 1993;Zwietering et al, 1994a). Although the product μ max × λ is not always constant (Koseki and Nonaka, 2012), it generally ranges between approximately 0 and 4 (Koutsoumanis et al, 2006;Zwietering et al, 1994a). In the present study, the lag time was estimated assuming that μ max × λ = 1 and μ max × λ = 4.…”
Section: Validation Of Modelmentioning
confidence: 96%
“…Our results indicate that the quantification of k is more influenced by possibly uncommon shapes, induced by high stressful conditions, than the other parameters l, A and AUC, resulting both in negative values and broad CI. Modelling of bacterial lag time is complicated because the mechanisms governing lag time are not fully understood (Swinnen et al, 2004;Kosekia & Nonaka, 2012). It is known that bacterial lag time is influenced not only by current environmental conditions but also by multiple other factors, such as previous growth conditions (Swinnen et al, 2004;Ryall et al, 2012), initial cell counts (Baranyi & Pin, 1999) and stochastic variability (McKellar & Hawke, 2006;Koutsoumanis, 2008;Ginovart et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, the effect of changing conditions could be predicted, such as the impact of transient temperature (ComBase [http://www.combase.cc], Sym’Previus [http://www.symprevius.net]), but, generally, only constant parameters are taken into account. If the environmental conditions and their impacts are taken into account on the μ max (using, e.g., the cardinal values), these are generally neglected on the lag phase in these kinds of models (Koseki and Nonaka ).…”
Section: Impact Of O2/co2 Gases On the Growth Of Microorganisms: Predmentioning
confidence: 99%